2018
DOI: 10.1159/000495254
|View full text |Cite
|
Sign up to set email alerts
|

Taxifolin Inhibits Receptor Activator of NF-κB Ligand-Induced Osteoclastogenesis of Human Bone Marrow-Derived Macrophages in vitro and Prevents Lipopolysaccharide-Induced Bone Loss in vivo

Abstract: It has been reported that taxifolin inhibit osteoclastogenesis in RAW264.7 cells. In our research, the inhibition effects of taxifolin on the osteoclastogenesis of human bone marrow-derived macrophages (BMMs) induced by receptor activator of NF-κB ligand (RANKL) as well as the protection effects in lipopolysaccharide-induced bone lysis mouse model have been demonstrated. In vitro, taxifolin inhibited RANKL-induced osteoclast differentiation of human BMMs without cytotoxicity. Moreover, taxifolin significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…The mechanisms of antioxidative and anti-inflammatory function of taxifolin include the inhibition of NF- κ B ( 14 , 19 ) and JAK2/STAT3 signaling ( 36 ). Taxifolin inhibited inflammation via suppressing the activation of NF- κ B, which can regulate the gene transcription of inflammatory cytokines ( 37 ). Cytokines IL-1β, IL-6, and TNF-α can activate NF- κ B phosphorylation in colitis.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of antioxidative and anti-inflammatory function of taxifolin include the inhibition of NF- κ B ( 14 , 19 ) and JAK2/STAT3 signaling ( 36 ). Taxifolin inhibited inflammation via suppressing the activation of NF- κ B, which can regulate the gene transcription of inflammatory cytokines ( 37 ). Cytokines IL-1β, IL-6, and TNF-α can activate NF- κ B phosphorylation in colitis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DAPI 1 mg/ml was treated for 10 min and then observed using a fluorescence microscope, Olympus IX 71‐F3 2PH (Olympus, Japan). Also, the area of actin ring formation relative to the total area was measured and quantified as a percentage (Zhang, Wang, Yang, Gao, & Tang, ). Image‐J software Version 1.52i (USA) was used to evaluate the area.…”
Section: Methodsmentioning
confidence: 99%
“…As osteoclast precursor cells, bone marrow-derived macrophages, which arise from haematopoietic cell lines, play a key role in bone remodelling during tooth movement [9]. Mesenchymal stem cells can regulate macrophage polarization by secreting a variety of biological and immunoregulatory factors to complete bone remodelling [10]. Some studies have confirmed that humanderived stem cells promote osteoclast differentiation in macrophage lines [11].…”
Section: Introductionmentioning
confidence: 99%